2015
DOI: 10.4103/0975-7406.163511
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral squamous cell carcinoma of tongue in and around Davangere, Karnataka, India: A retrospective study over 13 years

Abstract: Aim:The aim was to determine the frequency and distribution of oral squamous cell carcinoma (OSCC) involving tongue among patients by studying biopsy specimens obtained from the archives of the Department of Oral and Maxillofacial Pathology, College of Dental Sciences, Davangere, Karnataka, India, during the past 13 years.Methodology:Data for the study were retrieved from the case records of patients. Analyzed clinical variables included age, sex, anatomical site, and histological diagnosis.Results:Of the 369 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 15 publications
7
23
3
Order By: Relevance
“…In several studies, preference for males varied among 48% and 86.4% [18][19][20][21][22][23] and the male frequency we found (53.3%) is within the above-mentioned range. In the literature, mean age is widely variable, it was from 64.3 to 47.5 years, 18,[21][22][23][24] and in our study, it was slightly lower (63.9 years).…”
Section: Agesupporting
confidence: 80%
See 3 more Smart Citations
“…In several studies, preference for males varied among 48% and 86.4% [18][19][20][21][22][23] and the male frequency we found (53.3%) is within the above-mentioned range. In the literature, mean age is widely variable, it was from 64.3 to 47.5 years, 18,[21][22][23][24] and in our study, it was slightly lower (63.9 years).…”
Section: Agesupporting
confidence: 80%
“…Our results are only similar to those from the Ramdass et al study, 21 but completely different to those found in other studies showing that the WD type was the most common followed by the moderately differentiated type. 18,22,23,24 It is interesting to note, that in this study, a high proportion of low risk patients developed SCCT. This data does not agree with previous studies showing that high risk patients comprise the high proportion of the analyzed samples.…”
Section: Microscopic Differentiationmentioning
confidence: 55%
See 2 more Smart Citations
“…Albuquerque et al [11] found 59.7% involving lateral borders of the tongue were the most frequent carcinoma. These results are similar to present study results, as we also found a most frequent site to be the lateral border of tongue and accounts for about 42.2%, 171 cases out of 405 studied.…”
Section: Discussionmentioning
confidence: 95%